Communication and behavioural disorders among children with hearing loss increases risk of mental health disorders - Shipley, M; Strazdins, L; Hogan, A; Purcell, A; Baker, Elise (My University, 2011)
Objective: This study examines the mental health and associated risk factors of children with hearing loss. Methods: A cross-sectional analysis of the impact of hearing loss among Australian children using data drawn from Wave 1 of the Longitudinal Study of Australian Children (2004) (LSAC) (n=4589). LSAC provides data which assesses family circumstances, children's hearing problems, chronic health conditions, social and emotional difficulties, communications disorders and language, motor skills and educational outcomes. Outcomes for children aged 4–5 years identified with hearing loss (n=93) were compared with 4,496 children without hearing loss. Results: Children with hearing loss showed elevated prevalence across most dimensions of emotional and behavioural difficulties, and on indicators of communication disorders, language and cognitive development, and motor skills. Reduced receptive language skills and increased difficulties understanding others were predictive of increased psychosocial difficulties in children with hearing problems. Conclusion: Australian children with hearing problems face multiple concurrent health and developmental problems. Moreover, children with hearing problems exhibit behavioural problems when they do not understand what is going on around them. Without appropriate interventions, these children are at risk of developing mental health disorders. Implications: An epidemiological study of hearing in children is indicated. Children with receptive hearing problems require access to amplification, communication training, and psychosocial support. Attention must also be given to building design to reduce physical barriers to hearing.
Australia and New Zealand Journal of Public Health
Keywords: Child Development -- Speech and Language; Health -- Mental; Child Development; Childhood and child development; Health and wellbeing; Health; Child Development; Mental; Speech and Language; Childhood and child development; Health and wellbeing